Immunomodulatory and regenerative potentials of breast milk, prematurity and children’s heart - E. N. Pavlyukova; M. V. Kolosova; G. V. Neklyudova; R. S. Karpov (Медицинская иммунология, 2024)
Recent expansion of fundamental knowledge on the physiology of lactation, and breast milk exosomes, stem cell biology, mother-child interactions from prenatal period to postnatal development requires a progressive, dynamic view from the scientific community and practicing physicians when analyzing known, generally accepted clinical phenomena and patterns (development of the immune system of infants and young children, natural and artificial feeding, features of postnatal development and growth of organs and tissues in children born prematurely). The components of the mother-breast-milk-infant triad are closely related to each other and influence developmental trajectory of the infant. According to modern concepts, breast milk of a nursing woman is a “living, metabolic / endocrine signaling system”, which may be considered an “immune organ” significant for postnatal growth and body programming of a premature baby. A valuable phenomenon of early postnatal development is actively discussed in the special literature, i,e., “microchimerism” caused by breastfeeding which, according to modern concepts, may play a key role in development of immune system and the whole body. Absence of protective (immunomodulatory and regenerative) effects of breast milk from a nursing woman on the spontaneous, uncorrectable impact of adverse factors of prematurity is likely predispose for remodeling and dysfunction of heart in prematurely born children, and, at longer range, in adults. The young children born prematurely show a unique cardiac phenotype characterized by reduced biventricular volume, relatively lower systolic and diastolic function, disproportionate muscle mass gain, clinically manifesting by increased risk of cardiovascular disease, hypertension, and decreased exercise tolerance. Hence, the premature birth may be considered a chronic disease state. Therefore, the natural feeding which provides a natural evolutionarily protective mechanism for the child’s heart should be attributed to the fundamental factors that play a vital role in prevention of cardiovascular diseases in prematurely born children and at later life periods.